Strategi Pendampingan Hybrid Koperasi-Perguruan Tinggi: Dampak terhadap Pengembangan Kapasitas dan Pertumbuhan UMKM Makanan Olahan - Farhat Abas (Yayasan Literasi Sains Indonesia, 2025)
This study examines the effectiveness of a hybrid mentoring model between cooperatives and universities in enhancing the performance of processed food MSMEs in South Tangerang. Using a qualitative case study approach, data was collected through in-depth interviews with 5 mentored MSMEs, 3 cooperative administrators, and 2 lecturers, along with program document analysis during February-April 2024. Findings indicate that this collaboration successfully increased MSMEs' average revenue by 22% over six months through joint coaching and training-linked financing schemes. Key success factors included the cooperative's allocation of 20% budget for mentoring, flexible training modules, and monthly evaluations by hybrid teams. Implementation challenges such as MSME resistance and communication gaps were overcome through boundary spanners. The study strengthens Contingency Theory by demonstrating the importance of adapting mentoring models to local contexts. Recommendations include establishing collaborative divisions within cooperatives, integrating programs into university curricula, and developing digital platforms by local governments. These findings offer practical contributions for strengthening inclusive and sustainable urban entrepreneurship ecosystems.